Slip Rates Along the Laohushan Fault and Spatial Variation in Slip Rate Along the Haiyuan Fault Zone. Issue 2 (17th February 2022) - Liu, Jinrui; Ren, Zhikun; Zhang, Huiping; Li, Chuanyou; Zhang, Zhuqi; Zheng, Wenjun; Li, Xuemei; Liu, Caicai
Abstract: The spatial pattern of slip rates along the Haiyuan fault zone may reveal deformation process along the northeastern margin of the Tibetan Plateau. By applying the 3D_Fault_Offsets code, we reevaluated the displacements of offset markers displaced by the Laohushan fault, the central segment of the Haiyuan fault zone. We introduced the Bayesian Age Model approach to provide optimum age control for the preserved offset markers. Multiple offsets and ages constrain the late Pleistocene slip rate to 4.4–4.8 mm/yr. The spatial pattern of strike‐slip rates of the Haiyuan fault zone indicates that the Madongshan and Liupanshan could be the main uplifts that absorbed the left‐lateral motion along the Haiyuan fault zone, due to a restraining bend between the Haiyuan and Qishan‐Mazhao fault zones. Furthermore, uniform slip rates along the main segments and slip rates decreasing toward fault tips are widely observed along some intensively studied strike‐slip faults, such as the Altyn Tagh, Kunlun, Death Valley‐Fish Lake Valley, Denali, San Andreas and Alpine faults. The results suggest that the constancy or similarity of the slip rates along the strike is closely related to block rotation and internal deformation, and the slip rates of strike‐slip faults usually change at the fault tip area converting from horizontal to vertical motion. In addition, strike‐slip fault can also take slip off of the main fault and distribute it between multiple active parallel strands. Key Points: The late Pleistocene slip rate of the Laohushan fault was reevaluated and the Miocene slip rate of the Laohushan fault was estimated By synthesizing the slip rates along the Haiyuan fault, the Madongshan and Liupanshan could be a restraining bend of the Haiyuan fault Slip rates along well‐studies strike‐slip faults were synthesized and changed at the restraining bend or fault termination